2007
DOI: 10.1051/apido:2006070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the queen on worker reproduction and new queen production in the bumble beeBombus terrestris

Abstract: -We tested the hypotheses that a non-volatile pheromone inhibiting worker egg-laying and queen development produced by Bombus terrestris queens has effects transferable (a) from workers to other workers or larvae, or (b) on wax. We subdivided small, young colonies with a single mesh screen (Experiment 1) and larger, older colonies with a double mesh screen (Experiment 2). One treatment (in both experiments) involved the transfer of workers, and one treatment (in Experiment 2 only) involved the transfer of wax,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Our results do not support the classical hypothesis that worker reproduction is inhibited by a queen pheromone Duchateau & Velthuis, 1988). It was reported by Lopez-Vaamonde et al (2007), that queenlessness causes earlier worker aggression. We do not fully understand the meaning of this difference but it could be explained by reproductive competition in relation to the mutual interests of the queen and workers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not support the classical hypothesis that worker reproduction is inhibited by a queen pheromone Duchateau & Velthuis, 1988). It was reported by Lopez-Vaamonde et al (2007), that queenlessness causes earlier worker aggression. We do not fully understand the meaning of this difference but it could be explained by reproductive competition in relation to the mutual interests of the queen and workers.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the classical hypothesis, pheromones produced by the founder queen inhibit ovarian development in the workers and prevent or delay their egg laying until the worker population reaches a certain size (van Honk et al, 1980;Roseler et al, 1981). However, it was shown that such pheromones are not spread by workers, although queenlessness does lead to earlier worker aggression (Lopez-Vaamonde et al, 2007). Nevertheless, according to Bloch & Hefetz (1999) the reproductive behavior of B. terrestris workers is inhibited by the queen, although the workers themselves also play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…In bumble bees, Bombus terrestris, direct contact with the queen is necessary for the inhibition of worker reproduction. However, these interactions do not appear to be aggressive in nature (Alaux et al, 2004;Lopez-Vaamonde et al, 2007), suggesting that a contact pheromone that inhibits worker reproduction may be present. In the sympatric, primitively eusocial paper wasp species, Ropalidia marginata and Ropalidia cyathiformis, it appears that R. cyathiformis queens rely primarily on physical aggression to establish reproductive dominance, while R. marginata queens appear to use chemicals produced in the Dufour's gland to mediate reproductive dominance, and are not physically aggressive (Kardile and Gadagkar, 2002;Bhadra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae are irreversibly determined from a totipotent state (i.e. in which larvae are capable of developing into either caste) towards worker development provided that, during a sensitive larval phase for 3–5 days after hatching (in the second instar), the colony queen is present and emitting a pheromonal signal 27 29 30 31 . It is hypothesized that, later in the colony cycle, the queen stops producing the pheromone, so allowing female larvae to develop as queens 30 31 32 .…”
mentioning
confidence: 99%